Viperin mutation is linked to immunity, immune cell dynamics, and metabolic alteration during VHSV infection in zebrafish - Shanaka, K. A. S. N.; Jung, Sumi; Madushani, K. P.; Kim, Myoung-Jin; Lee, Jehee (Frontiers in Immunology, 2023)
Viperin is a prominent antiviral protein found in animals. The primary function of Viperin is the production of ddhCTP, an inhibitory nucleotide involved in viral RNA synthesis. Studies in mammalian models have suggested that ddhCTP interferes with metabolic proteins. However, this hypothesis has yet to be tested in teleost. In this study, the role of Viperin in regulating metabolic alterations during viral hemorrhagic septicemia virus (VHSV) infection was tested. When infected with VHSV, viperin -/-fish showed considerably higher mortality rates. VHSV copy number and the expression of the NP gene were significantly increased in viperin -/-fish. Metabolic gene analysis revealed significant differences in soda, hif1a, fasn, and acc expression, indicating their impact on metabolism. Cholesterol analysis in zebrafish larvae during VHSV infection showed significant upregulation of cholesterol production without Viperin. In vitro analysis of ZF4 cells suggested a considerable reduction in lipid production and a significant upregulation of ROS generation with the over-expression of viperin. Neutrophil and macrophage recruitment were significantly modulated in viperin -/-fish compared to the WT fish. Thus, we have demonstrated that Viperin plays a role in interfering with metabolic alterations during VHSV infection.